2022
DOI: 10.47738/ijaim.v2i3.37
|View full text |Cite
|
Sign up to set email alerts
|

Small and Medium Enterprises (SMEs) with SWOT Analysis Method

Abstract: This study aims to determine the strengths, weaknesses, opportunities and threats to SMEs in utilizing social media as a marketing tool and to find out the most effective marketing strategies to run in order to increase sales. The method used is SWOT analysis, and in data processing using excel. In collecting data using a questionnaire method distributed in the January 2021 period with a total of 226 respondents. The results obtained by SMEs in utilizing social media as marketing are in quadrant I, which means… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…This matrix produced four sets of possible strategic alternatives for MFI development. This is adapted from [NO_PRINTED_FORM] [16], which is applied to the company. For more details, the strategies that have been prepared can be seen in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…This matrix produced four sets of possible strategic alternatives for MFI development. This is adapted from [NO_PRINTED_FORM] [16], which is applied to the company. For more details, the strategies that have been prepared can be seen in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Metode SWOT merupakan identifikasi faktor-faktor secara sistematis untuk membuat strategi organisasi, Analisis SWOT mencakup identifikasi pada kekuatan, kelemahan, peluang, dan ancaman yang mempengaruhi kinerja organisasi/perusahaan (Rakhmansyah et al, 2022)…”
Section: Swotunclassified
“…Relationship quality, as a significant dimension, has a positive impact on purchase intention (Bonsón Ponte et al, 2015;Lu et al, 2016;Ali, 2016), while satisfaction has also been shown to have a significant effect on purchase intention (Hsu and Lin, 2015;Le, 2021). Furthermore, customer loyalty is an important indicator that reflects a solid relationship between seller and buyer (Rakhmansyah et al, 2022;Ky Vien, 2021). Customer interactions through virtual channels also play a role in shaping ongoing customer loyalty (Schiffman and Kanuk, 2009).…”
Section: Relationship Quality and Two Customer Behavioral Outcomesmentioning
confidence: 99%